Larynx cancer: quality of life and voice after treatment - Rossi,Vaneli Colombo (2014)
INTRODUCTION: Treatment for patients with larynx cancer often results in a negative impact on their physical, social and psychological functions. OBJECTIVE: To evaluate quality of life and voice in patients treated for advanced laryngeal cancer as a consequence of surgery or exclusive chemoradiation. METHODS: Retrospective cohort study with 30 patients free of disease: 10 total laryngectomy patients without production of esophageal speech (EVS); 10 Total laryngectomy patients with tracheoesophageal voice (TEV) and 10 patients with laryngeal voice. Quality of life was measured by SF-36; Voice-Related Quality of Life (V-RQOL) and Voice Handicap Index (VHI) protocols, applied on the same day. RESULTS: The SF-36 demonstrated that patients who received chemoradiotherapy exclusively enjoyed a feature better quality of life than the group of TEV and EVS. In V-RQOL it was observed that the quality of life related to voice is lower than in the EVS. In the VHI group EVS presented higher scores for overall VHI, emotional, functional and organic. DISCUSSION: Quality of life and voice in patients treated with chemoradiotherapy was better than in patients treated surgically. CONCLUSION: The type of medical treatment selected in patients with laryngeal cancer can influence changes in quality of life and voice.